0877 Systematic Sleep Time Extension: A Novel Approach to Extending Sleep in Habitual Short Sleepers. (27th April 2018) - Grandner, M; Perlis, M; Parthasarathy, S; Pack, A
Abstract: Introduction: Few real-world strategies exist for increasing sleep duration. As with other health behaviors, short sleep may be relatively intractable, as people give up sleep for increased work time, social activities, etc. Accordingly, a protocol was developed to evaluate whether an individualized, systematic upward titration of sleep opportunity would result in increased sleep duration. Methods: The sleep extension intervention was conducted over 8 weeks and entailed (1) standardizing the sleep-wake schedule by assigning bed/wake times based on mean sleep ability determined by 2 weeks of sleep diary average total sleep time, and (2) increasing sleep opportunity by 15 minutes per week provided sleep efficiency remained at the standard CBTI cutoff of >90%. If sleep efficiency was moderate, no additional time was added for that week. If sleep efficiency was lower than 85%, sleep opportunity was reduced by 15 minutes for the week. Five men aged 26–51 (M=33.4) who self-reported ≤6 hours of habitual sleep and did not have other medical, psychiatric, or sleep disorders were recruited. Subjects were not recruited on the basis of motivation to increase sleep duration. Results: Based on electronic daily sleep diaries, mean sleep duration at Week 1 was 5.8 hours (SD=1.2 hours) with a corresponding mean sleep efficiency of 86.8% (SD=7.8%). By the end of 8 weeks, these were increased to a mean 7.4 hours (SD=1.4 hours) with a sleep efficiency of 93.6 (SD=3.5%). Mean increase in sleep duration was 97.25 minutes per person (SD=23.9, range=57.7–118.0, effect size d=1.23). A paired t-test was significant (t(4)=-9.10, p=0.0008). Conclusion: In summary, a "real-world, " data-driven protocol that slowly increases sleep opportunity can be effective in extending sleep duration. The cardio-metabolic and neurocognitive health benefits of such an effective intervention need to be explored. Support (If Any):